Insights into Host-Pathogen Interactions in Biofilm-Infected Wounds Reveal Possibilities for New Treatment Strategies - Hannah Trøstrup; Anne Sofie Boe Laulund; Claus Moser (MDPI AG, 2020)
Normal wound healing occurs in three phases-the inflammatory, the proliferative, and the remodeling phase. Chronic wounds are, for unknown reasons, arrested in the inflammatory phase. Bacterial biofilms may cause chronicity by arresting healing in the inflammatory state by mechanisms not fully understood. Pseudomonas aeruginosa, a common wound pathogen with remarkable abilities in avoiding host defense and developing microbial resistance by biofilm formation, is detrimental to wound healing in clinical studies. The host response towards P. aeruginosa biofilm-infection in chronic wounds and impact on wound healing is discussed and compared to our own results in a chronic murine wound model. The impact of P. aeruginosa biofilms can be described by determining alterations in the inflammatory response, growth factor profile, and count of leukocytes in blood. P. aeruginosa biofilms are capable of reducing the host response to the infection, despite a continuously sustained inflammatory reaction and resulting local tissue damage. A recent observation of in vivo synergism between immunomodulatory and antimicrobial S100A8/A9 and ciprofloxacin suggests its possible future therapeutic potential.